2021
DOI: 10.1386/jgvw_00035_1
|View full text |Cite
|
Sign up to set email alerts
|

The mind games have already started: An in-depth examination of trash talking in Counter-Strike: Global Offensive esports using practice theory

Abstract: Trash talking is a contentious and prevalent practice in traditional sports but few studies have examined its practice in esports ‐ a computer-mediated form of sports competition in videogaming. This study used practice theory to identify different forms and dialectical relationships of trash talking in Counter-Strike: Global Offensive. Fifty hours of structured observations of professional tournaments were conducted followed by semi-structured interviews with fifteen spectators/casual gamers. Inductive analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 48 publications
2
5
0
Order By: Relevance
“…This is also observed in other research where players defend the use of trash talk if it does not include sociocultural themes of racism, sexism, or homophobia (Hilvert-Bruce & Neill, 2020;Nakamura, 2012;Ortiz, 2019). In one of the few studies investigating trash talk in esports, preliminary insights by Irwin et al (2021) on how esport spectators observe the social norms of trash talk practice found that it was judged upon reflection of the context and motive of the act. However, understanding the boundaries to which specific behavior within the professional esports scene diverges from socially acceptable trash talk and unfair harassment has been limited.…”
supporting
confidence: 56%
See 4 more Smart Citations
“…This is also observed in other research where players defend the use of trash talk if it does not include sociocultural themes of racism, sexism, or homophobia (Hilvert-Bruce & Neill, 2020;Nakamura, 2012;Ortiz, 2019). In one of the few studies investigating trash talk in esports, preliminary insights by Irwin et al (2021) on how esport spectators observe the social norms of trash talk practice found that it was judged upon reflection of the context and motive of the act. However, understanding the boundaries to which specific behavior within the professional esports scene diverges from socially acceptable trash talk and unfair harassment has been limited.…”
supporting
confidence: 56%
“…Trash talking a target verbally is one of the most common forms of trash talk in literature (Conmy et al, 2013;McDermott & Lachlan, 2021) and, in this study, typically occurred in an In Real Life environment. For instance, LAN events are tournaments where players can be situated within the same physical setting-either on a stage in front of a crowd or in a studio on opposing sides of a room (Irwin et al, 2021;Taylor & Witkowski, 2010). In a studio where external sounds are limited, professional players can shout across the room toward their opponent.…”
Section: Actionsmentioning
confidence: 99%
See 3 more Smart Citations